Answer

Verified

386.4k+ views

**Hint:**First, we have to find out the time taken to travel $75$ km at a speed of${\text{x}}$ km/hr by using the formula. Also, we use the given data we construct another time. Then we equate it as to $3$ hours, after simplification we get the required answer.

**Formula used:**${\text{time = }}\dfrac{{{\text{distance }}}}{{{\text{speed}}}}{\text{ }}$

**Complete step-by-step solution:**

Let us assume the original speed is ${\text{x}}$.

Now, we construct a bus that travels at a ${\text{x}}$ speed for a distance of \[75\] km.

As we know,

${\text{time = }}\dfrac{{{\text{distance }}}}{{{\text{speed}}}}$

So, time taken to travel $75$ km at a speed of${\text{x}}$km/hr = ${\text{t = }}\dfrac{{{\text{75}}}}{{\text{x}}}....{\text{(1)}}$

Again, the bus travels a distance of $90$ km at an average speed of $10$ km/hr more than the first speed.

It means the new speed is $10$ km/hr more than the first speed i.e., ${\text{x + 10}}$

Then time taken to travel $90$ km at a speed of ${\text{x + 10}}$ km/hr = ${\text{t = }}\dfrac{{{\text{90}}}}{{{\text{x + 10}}}}{\text{ }}....{\text{(2)}}$

It is given that the total time taken to complete the journey was $3$ hours. It means, it takes $3$ hours to complete both the distance i.e, $(1)$ and $(2)$.

Therefore, \[3{\text{ = }}\dfrac{{{\text{75}}}}{{\text{x}}} + \dfrac{{{\text{90}}}}{{{\text{x + 10}}}}\]

Taking LCM on both sides, we get,

$ \Rightarrow 3 = \dfrac{{{\text{75}}\left( {{\text{x + 10}}} \right){\text{ + 90}}\left( {\text{x}} \right)}}{{{\text{x}}\left( {{\text{x + 10}}} \right)}}$

On multiply the bracket term and we get,

$ \Rightarrow 3 = \dfrac{{{\text{75x + 750 + 90x}}}}{{{{\text{x}}^2} + 10{\text{x}}}}$

On adding the numerator term

$ \Rightarrow 3 = \dfrac{{{\text{165x + 750 }}}}{{{{\text{x}}^2} + 10{\text{x}}}}$

Taking cross multiply we get,

$ \Rightarrow 3\left( {{{\text{x}}^2} + 10{\text{x}}} \right) = 16{\text{5x + 750 }}$

Let us multiply the bracket term and we get,

$ \Rightarrow 3{{\text{x}}^2} + 30{\text{x}} = 16{\text{5x + 750 }}$

Here we can write it as equating form and we get,

$ \Rightarrow 3{{\text{x}}^2} + 30{\text{x - }}16{\text{5x - 750 = 0}}$

Dividing $3$ on both sides,

$ \Rightarrow 3{{\text{x}}^2} + 10{\text{x}} - 55{\text{x - 750 = 0}}$

On adding the same variable term and we get,

$ \Rightarrow {{\text{x}}^2}{\text{ - }}4{\text{5x - 250 = 0}}$

On splitting the \[x\]term and we get

$ \Rightarrow {{\text{x}}^2} - {\text{50x + 5x - 250 = 0}}$

Taking common variables out,

$ \Rightarrow {\text{x}}\left( {{\text{x - 50}}} \right){\text{ + 5}}\left( {{\text{x - 50}}} \right) = 0$

Again we take a common term and we get,

$ \Rightarrow \left( {{\text{x - 50}}} \right)\left( {{\text{x + 5}}} \right){\text{ = }}0$

On equate the term and we get,

$\left( {{\text{x - 50}}} \right){\text{ = 0 or }}\left( {{\text{x + 5}}} \right){\text{ = 0}}$

We can rewrite it as,

${\text{x = 50 or x = - 5}}$

Since speed cannot be in negative, ${\text{x}} \ne - 5$

Therefore ${\text{x = 50km/hr}}$

**So the original speed is ${\text{50km/hr}}$.**

**Note:**Here is another way to find roots from the quadratic equation formed,

Formula to find root value, ${\text{x = }}\dfrac{{{{ - b \pm }}\sqrt {{{\text{b}}^{\text{2}}}{\text{ - 4ac}}} }}{{{\text{2a}}}}$

Now we have a quadratic equation, ${{\text{x}}^2}{\text{ - }}4{\text{5x - 250 = 0}}$

Here, we have given values,

${\text{a}} = 1$

${\text{b}} = - 45$

${\text{c}} = - 250$

Now, we putting the values and we get,

${\text{x}} = \dfrac{{ - \left( { - 45} \right) \pm \sqrt {{{45}^2} - 4(1)( - 250)} }}{{2(1)}}$

On squaring the values and multiply we get,

${\text{x}} = \dfrac{{45 \pm \sqrt {2025 + 1000} }}{2}$

We split the equation as follows:

${\text{x}} = \dfrac{{45 + \sqrt {3025} }}{2},{\text{x}} = \dfrac{{45 - \sqrt {3025} }}{2}$

On squaring the root value and we get,

${\text{x}} = \dfrac{{45 + 55}}{2},{\text{x}} = \dfrac{{45 - 55}}{2}$

Let us add the term and we get,

${\text{x}} = \dfrac{{100}}{2},{\text{x}} = \dfrac{{ - 10}}{2}$

Let us divide the term and we get,

${\text{x = 50 / x = - 5}}$

Since speed cannot be in negative, ${\text{x}} \ne - 5$

Therefore ${\text{x = 50km/hr}}$

Recently Updated Pages

How do you find slope point slope slope intercept standard class 12 maths CBSE

How do you find B1 We know that B2B+2I3 class 12 maths CBSE

How do you integrate int dfracxsqrt x2 + 9 dx class 12 maths CBSE

How do you integrate int left dfracx2 1x + 1 right class 12 maths CBSE

How do you find the critical points of yx2sin x on class 12 maths CBSE

How do you find the general solution to dfracdydx class 12 maths CBSE

Trending doubts

The provincial president of the constituent assembly class 11 social science CBSE

Gersoppa waterfall is located in AGuyana BUganda C class 9 social science CBSE

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

The hundru falls is in A Chota Nagpur Plateau B Calcutta class 8 social science CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE